2012
DOI: 10.1097/brs.0b013e3182283102
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Extensive Extratemporal Hyperpneumatization of the Skull Base Including the Cervical Spine

Abstract: Atypical radiolucency may represent a very rare benign hyperpneumatization of the skull base, which may include the craniocervical junction. Because of microfractures of the thinned and consecutive, less stable bones, this also can lead to free air and soft-tissue emphysema, which has not been described previously. Special care should be taken to identify epidural free air because of a possible communication of the epidural space with the external environment. Harmful activities and especially high-speed traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Pneumatised and weakened cervical vertebrae are more susceptible to traumatic injury, and the spread of air across the synovial joints of the craniocervical junction raises the possibility of spread of pathogens from the nasopharynx and middle ear. Treatment reported by other authors has ranged from advising against performing the Valsalva manoeuvre, 6 through steroid nasal spays, 5 to myringotomy and grommet insertion, 3 , 4 and in one case surgical exploration and obliteration of airspaces using bone and fat grafts 7 . As our case demonstrates, addressing the cause of raised middle-ear pressure may result in both a rapid improvement in symptoms and a reversal of the pathological process.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Pneumatised and weakened cervical vertebrae are more susceptible to traumatic injury, and the spread of air across the synovial joints of the craniocervical junction raises the possibility of spread of pathogens from the nasopharynx and middle ear. Treatment reported by other authors has ranged from advising against performing the Valsalva manoeuvre, 6 through steroid nasal spays, 5 to myringotomy and grommet insertion, 3 , 4 and in one case surgical exploration and obliteration of airspaces using bone and fat grafts 7 . As our case demonstrates, addressing the cause of raised middle-ear pressure may result in both a rapid improvement in symptoms and a reversal of the pathological process.…”
Section: Discussionmentioning
confidence: 70%
“…There are very few other cases in the literature of skull base hyperpneumatisation involving the upper cervical vertebrae; however, all have in common a history of raised middle-ear pressure, minor trauma or both. [3][4][5][6][7][8] The most intriguing aspect of this condition is the fact that the pneumatisation process is able to cross seemingly intact synchondroses and joints. Both Turowski et al 4 and Littrell et al 5 Whilst the former authors proposed a mechanism of micro-fractures caused by pressure changes in the mastoid air cells, the latter supported the eustachian tube ball-valve theory, and suggested that persistently raised middle-ear pressure could lead to an erosive process of bony destruction capable of crossing the temporo-occipital synchrondosis and atlanto-occipital joints.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, patients have a chronic history of repetitive VM (4,5,8,10,11,13,19). Additional potential associations with CCP that may influence a middle ear pressure differential or induce VM include airline travel (10,11,16), high-altitude skiing (11,16), chronic cough (7), wind instrument playing (1), weight-lifting (2), and SCUBA/free diving (9,15).…”
Section: Epithelium (18) So It Is Likely That Ccp Occurs After Normamentioning
confidence: 99%
“…Notably, Madeline actually found occipitomastoid suture closure to be earlier in boys than girls (15.0 years versus 18.0 years for grade 4 closure) (22). Although trauma has been described in CCP cases, no causal association can be concluded since acute trauma may have led to imaging that found CCP either as an incidental finding or on the basis of a pathologic fracture (3)(4)(5)8,10,13,15,17,18,20). Moreover, a history of remote head trauma can be elicited quite commonly in the general population.…”
Section: Epithelium (18) So It Is Likely That Ccp Occurs After Normamentioning
confidence: 99%
See 1 more Smart Citation